2021
DOI: 10.1371/journal.pone.0249832
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer microbiota characterization: Prevalence of enteric and potentially pathogenic bacteria in cancer tissues

Abstract: Following recent findings linking the human gut microbiota to gastrointestinal cancer and its treatment, the plausible relationship between lung microbiota and pulmonary cancer is explored. This study aims at characterizing the intratumoral and adjacent healthy tissue microbiota by applying a 16S rRNA gene amplicon sequencing protocol to tissue samples of 29 non-small cancer patients. Emphasis was put on contaminant management and a comprehensive comparison of bacterial composition between cancerous and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…We did not observe a significant difference in overall microbiome composition between paired tumor and normal lung samples in our study, with composition being more similar within than between patients. Similar overall composition for paired tumor and normal lung is consistent with our previous pilot study [ 21 ] and other studies that have compared tumor and normal lung samples [ 18 , 55 , 56 , 62 65 ]. Some of these studies have observed differences in specific taxa between paired tumor and normal lung samples, including a meta-analysis of 5 studies which found decreased abundance of Actinobacteria, Corynebacterium , Lachnoanaerobaculum , and Halomonas in tumor compared to adjacent normal lung [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…We did not observe a significant difference in overall microbiome composition between paired tumor and normal lung samples in our study, with composition being more similar within than between patients. Similar overall composition for paired tumor and normal lung is consistent with our previous pilot study [ 21 ] and other studies that have compared tumor and normal lung samples [ 18 , 55 , 56 , 62 65 ]. Some of these studies have observed differences in specific taxa between paired tumor and normal lung samples, including a meta-analysis of 5 studies which found decreased abundance of Actinobacteria, Corynebacterium , Lachnoanaerobaculum , and Halomonas in tumor compared to adjacent normal lung [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…If the intestinal microbiota increases the effect of NAD boosting drugs, their concomitant use with antimicrobial agents should be prescribed only in patients where the presence of neoplastic disease can be ruled out. Bacteria are frequently associated with tumors ( Xu et al, 2020 ; Dumont-Leblond et al, 2021 ); for instance, the bronchial environments of lung tumors bronchial is enriched in Streptococcus harboring PncA nicotine amidase ( Bello et al, 2021 ). The activity of this bacterial protein might protect neoplastic tissues from NAD-targeting anti-cancer drugs by supplying nicotinic acid to the tumor cells, feeding the deamidated biosynthesis pathway to fulfill their high demand for NAD.…”
Section: Discussion Microbiota Modulation and Drugs Acting On Nad Met...mentioning
confidence: 99%
“…Tissue resident microbes have been found to be both cancer promoting and cancer preventing. In addition to their role in cancer progression, the microbiota is also critical for the metabolism of multiple drugs and xenobiotics, thus determining therapy response and prognosis in cancer patients. Gut microbes mediate the biotransformation of drugs via multiple chemical reactions including modification and removal of functional groups, proteolysis, denitration, deconjugation, amine metabolism, acetylation, and isoxazole scission. , They can affect the absorption of drugs as well as hinder radiotherapy. , Phylogenetic stratification of tissue resident microbiota reveals greater variability in less abundant microbes at species and strain levels rather than differences at class and phylum levels between breast cancer patients and healthy individuals. , This suggests the involvement of a few specific microbes in carcinogenesis. Certain pathogenic microbes are known to synthesize potent small molecules or genotoxins capable of inducing oncogenic signaling cascades in eukaryotic cells and metabolically rewire them.…”
Section: Discussionmentioning
confidence: 99%